Using MySQL databases with Python (Packt Publishing, 2019)
"Today databases are highly valued as they allow users to effectively manage, access, and update data. MySQL is one of the most popular databases and has a wide variety of applications in e-commerce, data warehousing, and website management. When combined with Python, one of the most popular and powerful programming languages today, you'll be able to manage data efficiently and systematically. In this course, you'll get started by understanding the basics of using MySQL with Python. You'll learn how to install MySQL and Python, before going on to develop databases. In addition to this, you'll explore the technique of creating tables for safely storing data. The course will then guide you on how to add, sort, and retrieve data through functions such as INSERT, ORDER BY, and SELECT. As you progress, you'll be equipped with the knowledge of inserting a single record as well as multiple records into a table. Toward the end, you will discover clauses such as WHERE and LIKE, and later learn to update records. By the end of this course, you will have learned how to confidently use Python with MySQL for your database management needs."--Resource description page